Governance Reforms in Federally Administered Tribal Areas (FATA) of Pakistan: The Past and Present - Altaf Ullah (Journal of Political Studies, 2015)
Governance of Federally Administered Tribal Areas of Pakistan is different in its nature and essence than other parts of the state. The theoretical framework for the governance of these areas has been enshrined in the historical regulation called Frontier Crimes Regulation (FCR) designed and implemented by the colonial government in British India during 19th century in order to achieve its specific ends. FATA became an integral part of Pakistan immediately after the great divide of August, 1947. The newly established state of Pakistan co-opted the same Regulation to govern these areas directly. Despite of so many shortfalls and drawbacks it was executed to maintain status quo in tribal areas of the country. Since then the state could neither fully integrate these areas in its fold nor could properly introduce such reforms which could bring tribal areas at par with other parts of the country. The legaladministrative mechanism of FATA which bestows more powers in the hands of political administration under FCR is basically responsible for the miseries of its downtrodden populace and the miserable condition of these areas as well. The present research endeavour seeks to observe whether the proverbial notion of “power corrupts and absolute power corrupts absolutely” is applicable to FATA or not. It also highlights that how and to which extent the recent governance reforms introduced via Frontier Crimes (Amendment) Regulation 2011, could curtail the power of political administration and safeguard rights of the people of FATA.